2022
DOI: 10.1002/app.53306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsolvent on the structures and properties of poly(arylene ether nitrile) films prepared by the phase inversion method

Abstract: In this study, a series of nonsolvents including ethyl acetate (EAC), acetic acid (HAC), n-butyl alcohol (NBA), iso-propyl alcohol (IPA) and ethanol (EA) were selected during the phase inversion process of poly(arylene ether nitrile) (PEN) films. The mechanism of film formation was tightly related with the interactions among polymer, solvent and nonsolvent. In the case of EAC, the aggregated sphere in P-EAC confirmed the in situ aggregate mechanism of polymer chains during the phase inversion process. As the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…After comparison and analysis, we found that the 3 wt% PEN/fullerene composite film and D20AF‐PEN‐280 had lower dielectric constants and dielectric losses, and the mechanical and mechanical properties of PEN‐2 were not much different from them, but the peel strength was able to reach 12.79 N/cm, which is 2–3 times higher than them. Wang et al 36 exploited the interaction between non‐solvent and polymer, and the introduction of pores in PEN films could reduce the density of the films and thus the dielectric constant. Among them, the dielectric constants of P‐EAC and P‐EA reached the standard for low dielectric constant materials (<2.5).…”
Section: Resultsmentioning
confidence: 99%
“…After comparison and analysis, we found that the 3 wt% PEN/fullerene composite film and D20AF‐PEN‐280 had lower dielectric constants and dielectric losses, and the mechanical and mechanical properties of PEN‐2 were not much different from them, but the peel strength was able to reach 12.79 N/cm, which is 2–3 times higher than them. Wang et al 36 exploited the interaction between non‐solvent and polymer, and the introduction of pores in PEN films could reduce the density of the films and thus the dielectric constant. Among them, the dielectric constants of P‐EAC and P‐EA reached the standard for low dielectric constant materials (<2.5).…”
Section: Resultsmentioning
confidence: 99%